2011
DOI: 10.1002/ejlt.201000488
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cocoa butter substitutes, milk fat and cocoa butter mixtures

Abstract: The melting properties and polymorphic behavior of binary and ternary blends of cocoa butter substitutes (CBS), cocoa butter (CB), and milk fat (MF) were studied by using pulsed nuclear magnetic resonance (NMR), differential scanning calorimetry (DSC), and X-ray diffractometry (XRD). Hydrogenated palm kernel stearin (HPKS) and hydrogenated palm kernel olein (HPKO) were chosen as the two CBS feedstock fats. Both CBS/CB binary blends displayed significant eutectic behaviors. Multiple melting peaks and eutectic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…1), possibly due to its high content of SSS TAGs ( Table 4). The phase behavior of fat mixtures can be explained by iso-solid phase diagrams [20], which have been used to illustrate the eutectic and monotectic effects as it is useful to understand the compatibility of mixed fat systems at a given temperature [21]. For example, the eutectic effect occurs when theoretically the contour lines of constant SFC are not straight, with some blend compositions having lower melting temperatures than expected.…”
Section: Solid Fat Content and Iso-solid Diagrams Of The Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), possibly due to its high content of SSS TAGs ( Table 4). The phase behavior of fat mixtures can be explained by iso-solid phase diagrams [20], which have been used to illustrate the eutectic and monotectic effects as it is useful to understand the compatibility of mixed fat systems at a given temperature [21]. For example, the eutectic effect occurs when theoretically the contour lines of constant SFC are not straight, with some blend compositions having lower melting temperatures than expected.…”
Section: Solid Fat Content and Iso-solid Diagrams Of The Blendsmentioning
confidence: 99%
“…In the present study, the amounts of β′ 1 and β′ 2 crystals were found to be higher than CB for all the mixtures, while the amount of β 2 crystal was reasonably lower compared to commercial CB. In a previous study, more than 70 % β′ crystals compared to the β crystal have been reported to be desirable for compound chocolates and coatings [21]. Therefore, 20-40 % PMF in RBDPKO, 30-50 % RBDPS in RBDPKO and 50-80 % of PMF in RBDPS mixtures may be used as CBSs in compound chocolates.…”
Section: Polymorphismsmentioning
confidence: 99%
“…The stable polymorph (β) is typically preferred in chocolates and coatings because it melts at high melting temperature with small to moderate crystal sizes, allowing for smooth mouth-feel products [5]. The metastable β′ polymorph is desirable for confectionery fillings and compound chocolates because it melts at low temperature with a fine arrangement and a large surface area of solid crystals [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These modifications of lipid also affected the DSC thermograms. DSC is a common method for determining the melting characteristics of fats (Wang et al 2011). In the present study, the melting point of Doogh lipid samples increased during storage.…”
Section: Discussionmentioning
confidence: 98%